Otimização da gestão da eficiência produtiva industrial através da análise de dados: uma solução integrada com MS Power BI e Google Sheets - SILVA, Victor Messias de Abreu (2024)
This article will show the challenges, methodologies and results regarding the development of a tool for measuring and analyzing the productive efficiency of industrial equipment. This tool is of significant importance for managerial decision-making, through data analysis and information management. The advantages of opting for technological tools for industrial management are also presented, where the use of the MS Power BI tool is emphasized in generating dynamic dashboards together with the Google Sheets tool that acts as a spreadsheet manipulated by users and as a database to feed the Dashboards analyzed by company management. The project took place in a packaging industry located in the municipality of Castanhal-PA, in the years 2022 and 2023.